2016
DOI: 10.1002/mds.26803
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional and longitudinal multimodal structural imaging in prodromal Huntington's disease

Abstract: Objectives Diffusivity in white-matter tracts is abnormal throughout the brain in cross-sectional studies of prodromal Huntington’s disease. To date, longitudinal changes have not been observed. The present study investigated cross-sectional and longitudinal changes in white-matter diffusivity in relationship to the phase of prodromal Huntington’s progression, and compared them with changes in brain volumes and clinical variables that track disease progression. Methods Diffusion MRI profiles were studied ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 51 publications
4
31
0
Order By: Relevance
“…Many years of study have consistently shown that progressive changes in structural magnetic resonance imaging (and likely functional magnetic resonance imaging and magnetic resonance spectroscopy) begin well before manifest HD, and perhaps even before the period of prodromal HD. Blood and cerebrospinal fluid biomarkers, especially mutant Huntingtin (Htt) and neurofilament light‐chain levels, are becoming increasingly relevant.…”
Section: Issues For Discussionmentioning
confidence: 99%
“…Many years of study have consistently shown that progressive changes in structural magnetic resonance imaging (and likely functional magnetic resonance imaging and magnetic resonance spectroscopy) begin well before manifest HD, and perhaps even before the period of prodromal HD. Blood and cerebrospinal fluid biomarkers, especially mutant Huntingtin (Htt) and neurofilament light‐chain levels, are becoming increasingly relevant.…”
Section: Issues For Discussionmentioning
confidence: 99%
“…Given that the PREDICT‐HD study was both multi‐centered and longitudinal in nature, implementation of the standardized image acquisition protocol was heterogeneous secondary to multiple vendors (GE, Phillips, and Siemens) and different field strengths (1.5 and 3 Tesla), and culminated in more than 20 variations in MR acquisition. Details of the acquisition information can be found in previous PREDICT‐HD studies (Harrington et al, ; Misiura et al, ). Our study data is comprised of MPRAGE data from 3 T scanners at 21 collection sites.…”
Section: Methodsmentioning
confidence: 99%
“…Both cross-sectional and longitudinal studies of neurodegenerative disorders have reported encouraging results regarding the use of DWI as a biomarker for disease progression (Bozzali et al, 2002; Canu et al, 2010; Goveas et al, 2015; Gregory et al, 2015; Harrington et al, 2016; Mayo et al, 2017; Phillips et al, 2014; Phillips et al, 2016; Poudel et al, 2015; Stricker et al, 2009; Weaver et al, 2009; Weiler et al, 2015; Yu et al, 2009). While studies in PD have reported cross-sectional differences in DWI measures between PD and control subjects (Agosta et al, 2014; Bertrand et al, 2012; Duncan et al, 2016; Goveas et al, 2015; Hattori et al, 2012; Melzer et al, 2013; Rae et al, 2012; Zhang et al, 2011), information regarding differential progression of WM change between PD patients and normal aging adults is relatively limited (Melzer et al, 2015; Rossi et al, 2014; Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%